1997
DOI: 10.1021/bi971931z
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Phosphine Complexes of Technetium(III) as Transport Substrates of the Multidrug Resistance P-Glycoprotein and Functional Markers of P-Glycoprotein at the Blood−Brain Barrier

Abstract: The multidrug resistance (MDR1) P-glycoprotein functions as a broad specificity efflux transporter of structurally diverse natural product and xenobiotic compounds. P-glycoprotein also is an important component of the functional blood-brain barrier. To enable further studies of function and modulation of MDR1 P-glycoprotein in vitro and in vivo, two novel phosphine technetium(III) complexes were designed and characterized: trans-[2,2'-(1, 2-ethanediyldiimino)bis(1, 5-methoxy-5-methyl-4-oxo-hexenyl)]bis[methylb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
62
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 51 publications
(65 citation statements)
references
References 44 publications
3
62
0
Order By: Relevance
“…LY335979 did not enhance accumulation of Tc-Sestamibi in MCF-7 cells, providing further evidence that this cell line does not express MDR1 Pgp (6,24). Previously, our laboratory has shown that KB 8-5 cells accumulate ϳ50-fold less TcSestamibi than Pgp-negative parental KB 3-1 cells (17). Thus, these functional data are consistent with differences in relative expression of Pgp in MCF-7/MDR1 and KB 8-5 cells.…”
Section: Characterization Of Mcf-7/mdr1supporting
confidence: 85%
See 2 more Smart Citations
“…LY335979 did not enhance accumulation of Tc-Sestamibi in MCF-7 cells, providing further evidence that this cell line does not express MDR1 Pgp (6,24). Previously, our laboratory has shown that KB 8-5 cells accumulate ϳ50-fold less TcSestamibi than Pgp-negative parental KB 3-1 cells (17). Thus, these functional data are consistent with differences in relative expression of Pgp in MCF-7/MDR1 and KB 8-5 cells.…”
Section: Characterization Of Mcf-7/mdr1supporting
confidence: 85%
“…Clones of transfected cells were isolated and maintained in medium containing 1 mg/ml G418. Drug-sensitive (Pgp-negative) KB 3-1 and MDR (Pgp-positive) KB 8-5 human epidermoid carcinoma cells were grown and maintained as described (17).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sep-Pak purification (>95%) and quality control of the tracer were performed as previously described (25). Following intravenous injection, distribution of [ 99m Tc]Sestamibi in the brain and blood of Pgp WT and Pgp-null mice with or without coexpression of APPsw +/-was determined 5 minutes after injection as previously described (26,27 and are reported as mean ± SEM (n = 3-4) or ± range (n = 2).…”
Section: Methodsmentioning
confidence: 99%
“…Following administration of a gamma-emitting compound, gamma scintigraphic images can be acquired using a gamma camera, and distribution of the compound throughout the body can be examined. Of major significance to BBB transport, it has been shown that 99 m Tc-sestamibi and other related compounds, such as 99 m Tc-tetrofosmin and a novel technetium (III) complex ( 99 m Tc-Q58), have higher brain uptake in P-gp knockout mice compared with wild-type mice (Luker et al 1997;Chen et al 2000;Dyszlewski et al 2002), indicating that such technetium-labelled compounds may be used to assess P-gp transport activity in-vivo. Although this technique may be useful in characterizing efflux transporters and BBB permeability in disease states, it will have a limited role in screening of compounds for potential brain uptake.…”
Section: Imaging Techniquesmentioning
confidence: 99%